Impact of Mental Map on the Achievement of forth preparatory Grade Students and Improving Their Mental Habits in Arabic Syntax - Ismael Ibrahim, Saif (Opción, 2019)
The study was conducted in Iraq, the center of the province of Nineveh, aimed to identify (the impact of the mental map on the achievement of fourth grade students preparation and development of habits of mind they have in Arabic grammar). The study was based on the experimental design with partial con- trol with both pre and post tests. The research sample consisted of (75) stu- dents, who were deliberately selected from the fourth grade literary students, they were divided into two groups and in a simple random way, the experi- mental group consisted of (38) students and studied according to strategy The mental map and a control group consisted of (37) students and studied in the traditional way. To achieve the goal of the study, the researcher used two tools, an achievement test in the subjects of Arabic grammar, which are taught to the fourth grade literary students and the other measure the habits of mind. After data collection, analysis and statistical processing using T-test, the ex- perimental group showed superiority over the control group in the achieve- ment and development of habits of mind.